2007
DOI: 10.1111/j.1571-9979.2007.00152.x
|View full text |Cite
|
Sign up to set email alerts
|

The Secrets of Successful (and Unsuccessful) Mediators Continued: Studies Two and Three

Abstract: In a survey of 216 advocates in mediation, the successful mediator's ability to gain the confidence of the parties was cited as important to his or her success more frequently than were any of the skills used by the mediator to bring about agreement. This article discusses the means by which mediators gain the confidence of disputing parties. The article also discusses the different skill and attribute profiles of different successful mediators and the advocates' views of the reasons for mediator failure. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
52
1
7

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(64 citation statements)
references
References 5 publications
1
52
1
7
Order By: Relevance
“…Mediators gain the trust of disputants when they possess expertise relevant to the issues under dispute (Doney et al, 1998;Goldberg and Shaw, 2007). Therefore, it is important for audit committee members to possess the necessary expertise if they are to play a mediating role in resolving contentious accounting issues between auditors and management.…”
Section: Development Of Hypothesesmentioning
confidence: 99%
“…Mediators gain the trust of disputants when they possess expertise relevant to the issues under dispute (Doney et al, 1998;Goldberg and Shaw, 2007). Therefore, it is important for audit committee members to possess the necessary expertise if they are to play a mediating role in resolving contentious accounting issues between auditors and management.…”
Section: Development Of Hypothesesmentioning
confidence: 99%
“…152 Moreover, it has been theorised that women "are more likely to treat a negotiation as an event in a long-term relationship, one linked to a larger social context and concerned with fairness and sensitivity to others, while men see it as a one-time event with no direct consequences for future interactions", thus fuelling more co-operative behaviour by women. 154 Goldberg and Shaw (2007), p. 406. Despite the idea that women may be naturally more inclined towards the consensual, relational and harmonious nature of mediation practice, Goldberg and Shaw's recent work into the traits of successful mediators, found that "[f]emale mediators were not cited [by mediation advocates] significantly more or less often for being friendly and empathic than were male mediators, nor were female mediators cited significantly more or less often for their process or evaluative skills than were their male counterparts."…”
Section: Gender Issuesmentioning
confidence: 99%
“…Such factors seemed to outweigh any process skills that mediators may hold-Goldberg and Shaw (2007), p. 414. 100 According to Goldberg and Shaw's research into what determines a successful mediator, the central conclusion to be drawn is that a-if not the-core element in mediator success is the mediator's ability to establish a relationship of trust and confidence with the disputing parties.…”
mentioning
confidence: 99%
“…Recent studies show that the key to mediation success lies in the ability to develop a relationship of understanding and empathy with disputants (Goldberg & Shaw, 2007). While we agree that the experience of recognition is generally important for disputants (Bush & Folger, 2005), particularly the experience of emotion recognition is vital to transform the conflict and to contribute to parties' positive perceptions of the mediation (Jameson, Bodtker, & Linker, 2010;Jones & Bodtker, 2001).…”
mentioning
confidence: 98%